The implementation of EDDU as a source of ideas for digital German language teaching - Ardiyani, Dewi Kartika; Hidayat, Edy (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2021)
In the industrial revolution 4.0 era, digital media is an important instrument in all aspects, including in the field of education. Twenty first century teachers are required to have the abilities and skills to utilize media, including digital media. This study aims to provide information for German language teachers and find out their perceptions of the use of Erfolgreich Digital Deutsch Unterrichten (EDDU) media in the learning process. EDDU is an internet-based digital media in the form of learning package, containing materials and learning steps such as games or quizzes. This study implemented a qualitative approach. Data were collected through observations, Forum Group Discussion (FGD), and questionnaires, resulting in qualitative and quantitative data that were described descriptively. The study involved German teachers in Malang, Indonesia. Results of the study indicates that EDDU can be used as a multimedia alternative. It offers teaching ideas and materials that can help teachers to prepare their lessons and present the materials. By using EDDU, German language teachers are able to improve the convenience in their teaching. EDDU is shown to have followed Indonesian high schools syllabus, the materials in EDDU have provided supports for online learning. The activities inspired through EDDU can make their classes more active and attractive. Di era revolusi industri 4.0, media digital merupakan instrumen penting dalam segala aspek, termasuk dalam bidang pendidikan. Oleh karena itu, guru abad 21 dituntut untuk memiliki kemampuan dan kecakapan dalam memanfaatkan media, termasuk media digital. Penelitian ini bertujuan untuk memberikan informasi kepada guru bahasa Jerman dan mengetahui persepsi mereka terhadap penggunaan media digital Erfolgreich Digital Deutsch Unterrichten (EDDU) dalam pembelajaran. EDDU merupakan media berbasis internet berupa paket pembelajaran yang berisi materi dan langkah-langkah pembelajaran dalam bentuk permainan atau kuis. Penelitian ini menggunakan pendekatan kualitatif. Pengumpulan datanya menggunakan observasi, FGD, dan angket yang menghasilkan data kualitatif dan kuantitatif, serta dipaparkan secara deskriptif. Sumber datanya adalah guru bahasa Jerman di Malang, Indonesia. Studi ini menunjukkan bahwa media EDDU dapat digunakan sebagai alternatif multimedia. EDDU menawarkan ide mengajar dan materi-materi yang dapat membantu guru menyiapkan pembelajaran dan menyampaikan materi. Dengan menggunakan EDDU, guru bahasa Jerman mendapatkan kemudahan dalam mengajar. Materi dalam EDDU sesuai dengan silabus Sekolah Menengah Atas atau Madrasah Aliyah. Materi yang diberikan mendukung pembelajaran online, dan kegiatan dengan menggunakan EDDU dapat membuat kelas lebih aktif dan menarik.